How Brand Excitement Can Enhance Emotional Responses of Local Fashion Brands in Indonesia? : Moderating of Ethnocentrism - Cindy Suwandhi; Tengku Ezni Balqiah (APMBA (Asia Pacific Management and Business Application), 2017)
In the last few decennium, research pertaining to brand has gained the attention of many academician. Interest in further studies of matters related to it, such as brand love and brand engagement has increased tremendously as well. This study was conducted to examine the effect of brand love, brand image and brand personality on brand engagement with ethnocentrism as a moderating factor by using case study of local fashion brand in Indonesia. Respondents in this study were people who have purchased clothing items from a specific brand of local fashion. Data processing method used is Structural Equation Model (SEM). This study indicates that the excitement does not have a positive influence towards brand love, and brand image does not have a positive effect on word-of-mouth (WOM). Nonetheless, with the existence of ethnocentrism as moderating factor, excitement’s effect towards brand love and brand image were even greater. Hereafter, brand advocacy was finally formed by brand love’s positive effect towards WOM. This study demonstrated the importance of ethnocentrism in enhancing word of mouth, and father brand advocacy.